Sleep in the military : promoting healthy sleep among U.S. servicemembers - Troxel, Wendy M. (Research report (Rand Corporation), 2015)
Sleep disturbances are a common reaction to stress and are linked to a host of physical and mental health problems. Given the unprecedented demands placed on U.S. military forces since 2001, there has been growing concern about the prevalence and consequences of sleep problems for servicemembers. Sleep problems often follow a chronic course, persisting long after servicemembers return home from combat deployments, with consequences for their reintegration and the readiness and resiliency of the force. Therefore, it is critical to understand the role of sleep problems in servicemembers' health and functioning and the policies and programs available to promote healthy sleep. This report provides the first comprehensive review of sleep-related policies and programs across the U.S. Department of Defense (DoD), along with a set of actionable recommendations for DoD, commanders, researchers, and medical professionals who treat U.S. servicemembers. This multimethod study also examined the rates and correlates of sleep problems among post-deployed servicemembers, finding negative effects on mental health, daytime impairment, and perceived operational readiness. The research reviewed evidence-based interventions to treat sleep disturbances among servicemembers and veterans and exposed several individual- and system-level barriers to achieving healthy sleep. Implementing evidence-based treatments is just one step toward improving sleep across the force; as the research recommendations highlight, it is equally important that policies and programs also focus on preventing sleep problems and their consequences.